PENGARUH BPK, KARAKTERISTIK PEMERINTAH DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT KORUPSI PEMERINTAH DAERAH DI INDONESIA - Verawaty Verawaty (MBIA, 2019)
ABSTRACT This research was aimed to obtain empirical evidence about the influence of audit findings, follow-up to the results of recommendations and audit opinions on the level of local government corruption in Indonesia with the size of the government, capital expenditure and human development index as a control variable. The research sample was 30 provincial governments that met the criteria. The analysis technique was quantitative by using multiple linear regression. The results indicated that only follow-up recommendations had an influence on the level of corruption. The implication is that the regional government needs to be aware of violations of the laws and regulations during the process of government administration, especially for actions that can cause state losses.